Squid suckerin biomimetic peptides form amyloid-like crystals with robust mechanical properties - Hiew, Shu Hui (2018)
We present the self-assembly of fibers formed from a peptide sequence (A1H1) derived from suckerin proteins of squid sucker ring teeth (SRT). SRT are protein-only biopolymers with an unconventional set of physicochemical and mechanical properties including high elastic modulus coupled with thermoplastic behavior. We have identified a conserved peptide building block from suckerins that possess the ability to assemble into materials with similar mechanical properties as the native SRT. A1H1 displays amphiphilic characteristics and self-assembles from the bottom-up into mm-scale fibers initiated by the addition of a polar aprotic solvent. A1H1 fibers are thermally resistant up to 239 °C, coupled with an elastic modulus of ∼7.7 GPa, which can be explained by the tight packing of β-sheet-enriched crystalline building blocks as identified by wide-angle X-ray scattering (WAXS), with intersheet and interstrand distances of 5.37 and 4.38 Å, respectively. A compact packing of the peptides at their Ala-rich terminals within the fibers was confirmed from molecular dynamics simulations, and we propose a hierarchical model of fiber assembly of the mature peptide fiber.